UJI EFEKTIFITAS EKSTRAK BIJI PINANG (Arecha cathecu L.) TERHADAP MORTALITAS HAMA PENGGEREK POLONG KEDELAI (Etiella zinckenella Treitschke) DI LABORATORIUM - Desita Salbiah; Natasa Ika Putri (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
Pod Borer (Etiella zinckenella) is a major pest in soybean cultivation. The chemical pesticides used in agriculture are causing various detrimental effects on our health as well as on environment. Botanical pesticides such as betel nut (Areca catechu L.) is an alternative pest control to reduce the use of synthetic chemical pesticides. This research was conducted in the plant pest laboratory, Faculty of Agriculture, Riau University. This study was conducted in order to found a concentration of betel nut seed extract (Areca catechu L.) which is effective to control E. zinckenella in soybean crops. The experiment using a completely randomized design with six treatments. Betel nut seed extract concentration are 0 g L-1 of water, 20 g L-1 of water, 40 g L-1 of water, 60 g L-1 of water, 80 g L-1 of water, and 100 g L-1 of water and each treatment was repeated four times. The result showed 40 g L-1 of water of betel nut seed extract is effective concentration and able to kill 80% E. zinckenella larvae.